Development of the R263K Mutation to Dolutegravir in an HIV-1 Subtype D Virus Harboring 3 Class-Drug Resistance. (12th December 2018) - Ahmed, N; Flavell, S; Ferns, B; Frampton, D; Edwards, S G; Miller, R F; Grant, P; Nastouli, E; Gupta, R K
Abstract: Dolutegravir (DTG), a second-generation integrase strand-transfer inhibitor (INSTI), is equivalent or superior to current non-nucleotide reverse transcriptase inhibitors (NNRTIs), protease inhibitors (PIs), and first-generation INSTI-based antiretroviral regimens (ARVs). It has the potential to make big improvements in HIV control globally and within patients. This is perhaps the most "precious" HIV drug available. The integrase mutation R263K has been observed in tissue culture experiments and in patients treated with dolutegravir monotherapy in clinical trials. Globally, adherence and monitoring may be less than optimal and therefore DTG resistance more common. This is particularly important in low–middle-income countries, where patients may remain on failing regimens for longer periods of time and accumulate drug resistance. Data on this mutation in non–subtype B infections do not exist. We describe the first report of the R263K integrase mutation in a dolutegravir-exposed subtype D–infected individual with vertically acquired HIV. We have used deep sequencing of longitudinal samples to highlight the change in resistance over time while on a failing regimen. The case highlights that poorly adherent patients should not be offered dolutegravir even as part of a combination regimen and that protease inhibitors should be used preferentially.